Prediksi Curah Hujan Kota Manado Dengan Menggunakan Metode Autoregressive Moving Average (ARMA) - Adianto Pakkung; Djoni Hatidja; Jullia Titaley (Sam Ratulangi University, 2024)
This study aims to determine the best ARMA model for predicting Manado City rainfall using the ARMA method. The data used in this study is time series data, namely data on the monthly rainfall period of Manado City starting from September 2018 to August 2023. The results showed that the best model obtained was the ARMA model (1,11) with the equation . From the results of the rainfall prediction, Manado City has an accurate level of MAPE value of 56%, with consecutive predictions from September 2023 to March 2024 are 83.2 mm, 98.8 mm, 131.1 mm, 289.1 mm, 237.7 mm, 222.6 mm, 206.9 mm.